Tawakkal Concept Theological, Sociological Perspective, and Psychology in the Qur’an - Ahlaa Nafisah Fatimah; Gicica Mutiara Bintang; Nila Farhatun Nazilah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The concept of tawakkal in the Qur’an is often misunderstood as an attitude of surrender without effort, whereas essentially it reflects the integration of human endeavor and dependence on the will of God. Islamic Religious Education (PAI) as an instrument for forming religious character requires an in-depth study of this concept from various perspectives. This study aims to reveal the dimensions of tawakkal in the Qur’an through theological, sociological, and psychological approaches, and to answer the formulation of the problem of how is tawakkal in theological, sociological, and psychological perspectives? The research method used is library research with a qualitative descriptive approach. The main source of this study is the Qur’an, supported by literature on interpretation, Islamic psychology, sociology, and the thoughts of classical and contemporary Islamic figures such as Al-Ghazali, Fazlur Rahman, and Malik Badri. The results of the study show that theologically, tawakkal is a manifestation of monotheism and faith in the power of Allah which brings peace of mind. From a sociological perspective, tawakkal encourages collaboration, social responsibility, and building a resilient society. Meanwhile, from a psychological perspective, tawakkal becomes an effective spiritual coping strategy in improving mental health and emotional stability. The integration of these three perspectives enriches the development of a more holistic and contextual PAI curriculum. Tawakkal is not only a spiritual principle, but also a strategic solution in forming a strong, adaptive, and responsible Muslim personality amidst the challenges of modern life.